Patrols by the Traffic Unit to Prevent Accidents Along the North Beach Route of The Jurisdiction of Batang Resort Police - Muchammad Mahendra Ghani Adhitya Putra (Advances in Police Science Research Journal, 2022)
The Pantura line is a road made by Herman Willem Daendales that passes through several towns and regencies along the island of Java. Batang Regency is one of the regencies crossed by the Pantura route. Accidents often occur on this route by shown by their fluctuating numbers. These fluctuating numbers can be preventived by traffic patrols. The Batang Polres Satlantas, especially the Turjagwali Unit, have problems in carrying out patrols and increasing patrol efforts. This final project uses a qualitative approach with primary and secondary data sources at Polres Batang. This final project uses the previous two theses as a guide in the research literature. Based on the results of the author's analysis, the novelty contained in this paper is about the increase of the Satlantas patrol efforts, especially the Turjagwali Unit. Then, this final project uses management theory, organizational resource theory, and SWOT as well as the concept of effort, traffic units, and traffic accidents. The Turjagwali Traffic Unit has factual conditions in the field. Factual conditions are divided into two, namely initial conditions and influencing factors. The initial conditions of this writing are an explanation of the initial conditions supporting the implementation of patrols, the factual conditions of the implementation of Satlantas patrols, and the initial conditions in the form of increasing Satlantas patrol efforts. Then, there are influencing factors, namely internal and external factors. The steps for solving the problem are the solutions given by the author to the two problems. The first solution regarding the implementation of Satlantas patrols is to coordinate with internal and external parties, evenly distribute the members of the Turjagwali Unit, cooperate with local governments, and carry out more intense supervision through the WhatsApp application. Conclusion of this final project is the implementation of Satlantas patrols and forms of improvement. The Satlantas patrol efforts have not been optimal due to the increasing and decreasing number of accidents. So the author provides solutions in the form of problem solving to problems and suggestions.